2014
DOI: 10.1002/eji.201343994
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐related signaling events influence TLR9‐induced IL‐10 secretion in human B cells

Abstract: Suppressory B-cell function controls immune responses and is mainly dependent on IL-10 secretion. Pharmacological manipulation of B-cell-specific IL-10 synthesis could, thus, be therapeutically useful in B-cell chronic lymphocytic leukemia, transplantation, autoimmunity and sepsis. TLR are thought to play a protagonistic role in the formation of IL-10-secreting B cells. The aim of the study was to identify the molecular events selectively driving IL-10 production in TLR9-stimulated human B cells. Our data high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response. [35][36][37][38][39][40][41][42][43][44][45][46][47] In most studies, attention has been paid to intracellular calcium mobilization. However, TLRs may trigger calcium release from the ER and then STIM-ORAImediated calcium entry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response. [35][36][37][38][39][40][41][42][43][44][45][46][47] In most studies, attention has been paid to intracellular calcium mobilization. However, TLRs may trigger calcium release from the ER and then STIM-ORAImediated calcium entry.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway is generally considered to be divided into two types-canonical Wnt/β-catenin signaling and noncanonical Wnt signaling, which is mainly activated by 19 Wnt proteins identified in mammals [16].Wnt5a, a member of Wnt family, binds to the frizzled receptor and LRP5/6 co-receptors to regulate multiple signaling pathways [17], thereby altering TME by inducing adipocytes to dedifferentiate into fibroblast-like cells or mesenchymal cells [18]. Furthermore, Wnt5a was considered to participate in the differentiation of immune cell, including dendritic cells, B cells, as well as macrophages [19][20][21]. Previously, Wnt5a was mainly located in the TAMs of tumor stroma in breast cancer or basal cell carcinoma [22,23]; Smith and colleagues consistently found that Wnt5a was mostly expressed in the tumor stroma of CRC, especially in TAMs [24].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the IL-10 response to other MAMPs (25,(47)(48)(49). Monocytes/macrophages are early responders to S. aureus, and their phenotype would be highly influential in establishing the microenvironment that sets up subsequent adaptive responses.…”
Section: Discussionmentioning
confidence: 95%